Research on neuromorphic vision sensor and its applications - Yongsheng SANG; Renhao LI; Yaoqian LI; Qiangwei WANG; Yao MAO (物联网学报)
Neuromorphic vision sensor is a biologically inspired artificial neural system that mimics algorithmic behavior of biological vision systems,which has numerous advantages over standard vision sensors,such as high temporal resolution,low latency,low power,high dynamic range,etc.At first,a brief introduction to neuromorphic engineering,neuromorphic chips,and vision sensors was given.Then the main computing methods for neuromorphic vision were reviewed,including probability and statistics,spiking neural network and deep neural network.Finally,several kinds of applications based on neuromorphic vision sensors were given,such as simultaneous localization and mapping (SLAM),image reconstruction (IR),etc.A review of hardware,computing methods and applications for neuromorphic vision sensors was given,which provided a comprehensive reference for researchers.